(untitled) (Research, Society and Development, 2021)
Water is a key resource for urban, industrial and agricultural development, especially in the semi-arid region, where it is a scarce factor. In addition to the problem of the amount of water available to the population, some factors further hinder its availability, such as the discharge of untreated or improperly treated sewage, industrial and agricultural effluents and chemicals such as fertilizers. In this wake, it is pointed out that gray water, in semi-arid regions, tends to be exacerbatedly used, as it is a viable and sustainable alternative for water treatment. It should be noted that the parameters analyzed for the gray waters collected from the observation points of the units were: Electrical Conductivity (EC), pH, Turbidity and Dissolved Oxygen (OD). Thus, in light of the above, this article seeks to evaluate Units of Controlled Agricultural Production / UPAC with and without the presence of hydrocyclone in the process of treating gray water generated in a public laundry in the municipality of Cabaceiras, aiming at the reuse of Water.